Planar and Vertical Signals Control Cellular Differentiation and Patterning in the Mammalian Cochlea - Montcouquiol, Mireille (J Neurosci, 2003)
The sensory epithelium of the mammalian cochlea is composed of a regular mosaic of sensory hair cells and nonsensory supporting cells. During development, differentiation occurs in a gradient that progresses along the axis of the cochlea from base to apex. To begin to identify some of the factors that regulate this developmental process, the potential roles of planar and vertical signals were examined during early stages of cochlear development. We demonstrate roles for both underlying mesenchymal cells and adjacent epithelial cells in the differentiation and patterning of the sensory epithelium, and in particular in the development of mechanosensory hair cells. As development proceeds, the requirements for both planar and vertical signals decrease, and development of the sensory epithelium becomes essentially independent from these cues. Finally, we demonstrate that the temporal gradient of cellular differentiation is not dependent on planar signals within the developing sensory epithelium.